PROTOTYPE STEAM POWER PLANT (ANALISIS HEAT LOSS PADA UNIT BOILER FURNACE DAN SUPERHEATER) - Difa Putri Utami, Ayu; ., Zurohaina; Aswan, Arizal (KINETIKA, 2016)
The purpose of this experiment is to find a formula prototype steam power plant to find a solution to the crisis of electricity in rural areas. Has conducted a study to determine heat loss at for incineration in furnaces and boiler super heater unit. The fuel used is diesel and LPG fuel with a mass of different - different. The results obtained from the calculation of the importance of the loss of heat radiation in the boiler furnace of 5.6%, 2.66% convection heat loss and heat conduction loss amounted to 5.73%, on the theory that it should heat loss should not be more than 1%. Heat loss occurring in the steam power plant prototype unit is still quite large when viewed from PLTGU PLN Keramasan sector with a heat loss in radiasi, conduction and convection. Heat loss can be mitigated in several ways one of them is a good insulator technique using cement or asbestos in accordance with the value of conductivity that need and can be determined from the results of the design calculations.